PENGARUH SOCIAL MEDIA MARKETING DAN INOVASI PRODUK TERHADAP BUSINESS PERFORMANCE PADA SENTRA INDUSTRI KERIPIK TEMPE “SANAN” KOTA MALANG - Dhakirah, Sanita; Nisa, Nurul Hidayatin; Khabibah, Umi (Jurnal Riset Entrepreneurship, 2024)
This study analyzes the impact of Social Media Marketing and Product Innovation on business performance in the tempe chip industry at Sentra Tempe Sanan, Malang City. Despite increasing competition from new culinary businesses leveraging social media and innovative products, the tempe chip industry in Sanan has maintained its market presence.Using regression analysis, the study finds that Social Media Marketing significantly improves business performance, enhancing brand awareness and customer engagement. Product Innovation also positively impacts performance, increasing customer numbers, creativity, and profits. Together, these factors explain 69% of the variation in business performance at Sentra Tempe Sanan.The findings suggest that optimizing social media marketing and continuous product innovation are crucial for sustaining competitiveness in the local market. This research offers practical insights for tempe chip producers in Sanan to improve their business strategies.